2021
DOI: 10.1055/s-0041-1729151
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bony Injuries of Hand and Wrist

Abstract: Acute bony injuries to the hand and wrist are very common after a fall on an outstretched hand. In the wrist, distal radius fractures are the most common; isolated distal ulna fractures are uncommon. More serious injuries to the wrist include complicated fracture-dislocation injuries such as perilunate dislocations. At the carpal level, scaphoid fractures are the most common followed by fractures of the dorsal side of the triquetrum. The metacarpals often fracture, most commonly the base of the thumb and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The most common injuries to the distal ulna are the ulnar styloid fractures, usually combined with distal radius fractures and Galeazzi's fracture of the mid to lower diaphysis of the distal radius with dislocation of the distal radioulnar joint (DRUJ). Posttraumatic instability of the DRUJ with subluxation generally follows injuries of the triangular fibrocartilage complex (TFCC) or of the ulnar styloid to which the TFC attaches [52]. The TFCC is frequently affected by fractures of the distal radius [53].…”
Section: Ulnar-sided Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common injuries to the distal ulna are the ulnar styloid fractures, usually combined with distal radius fractures and Galeazzi's fracture of the mid to lower diaphysis of the distal radius with dislocation of the distal radioulnar joint (DRUJ). Posttraumatic instability of the DRUJ with subluxation generally follows injuries of the triangular fibrocartilage complex (TFCC) or of the ulnar styloid to which the TFC attaches [52]. The TFCC is frequently affected by fractures of the distal radius [53].…”
Section: Ulnar-sided Injuriesmentioning
confidence: 99%
“…The mechanisms of injury in triquetrum fractures could be a dorsal bone avulsion by the extrinsic dorsal radiocarpal (DRC) ligament or the dorsal band of the lunotriquetral intrinsic ligament, impaction by the ulnar styloid or shearing by the proximal pole of the hamate. Avulsions of the dorsal rim are more frequent, occurring after a fall with the wrist in extreme flexion [5,52,56,57]. Becce et al reported that dorsal fractures of the triquetrum are frequently associated with DRT ligament injuries [58].…”
Section: Ulnar-sided Injuriesmentioning
confidence: 99%
“…While previously described, limited literature exists regarding the applicability of dorsal spanning plate (DSP) fixation in perilunate injuries [ 5 , 12 ]. Of note, due to the ambiguity of LDs being referred to interchangeably as perilunate dislocations (PLD) in the literature, this study utilizes the location of the capitate and lunate bones in comparison to the distal radius for nomenclature [ 6 , 13 ]. Malalignment of the capitate is a PLD; while lunate translation is a LD [ 6 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, associated soft tissue injuries (e.g., intrinsic scapholunate and lunotriquetral ligament, triangular fibrocartilage with or without concomitant distal radioulnar joint instability) are reported with high incidence [ 3 ]; MRI evaluation is crucial for the detection of these soft tissue injuries [ 4 ]. Additionally, MRI is used to identify potential radiographically occult fractures, such as associated occult scaphoid fractures [ 5 ]. More than 60% of patients diagnosed with distal radius fracture undergo surgical correction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%